Why do some countries produce more capital intensive output than others? - Toukan, Amjad (2016)
Interested in how does the quality of governance in a country affect the ratio of the value added share of capital intensive goods to the value added share of labor intensive goods, I am testing the hypothesis that the ratio of the value added share of capital intensive goods to the value added share of labor intensive goods is higher for countries that have better quality of governance. The intuitive explanation of my hypothesis is that the risk of expropriation by corrupt government officials is higher in the case of capital-intensive projects due to the larger size of the prize (many economists argue that it is easier for a corrupt government official to expropriate large non-standard capital-intensive projects as opposed to smaller standardized labor-intensive projects), so in countries where the quality of governance is low, investors prefer to invest in labor-intensive projects with lower output per worker instead of capital-intensive projects with higher output per worker. In my analysis I develop a game theoretic model and conduct an empirical analysis to test my hypothesis. In my game theoretic analysis I model the interaction between firms and corrupt government officials as a contest while allowing for international variability in the quality of governance. Based on my model I offer an explanation for the variation in physical capital intensity across countries where the model predictions show that a lower quality of governance in a country results in a decrease in the output of capital-intensive goods and an increase in the output of labor-intensive goods. In conducting panel data regressions (17 developing countries and 23 OECD countries over a period of twelve years 1982-1995), controlling for time and country fixed effects as well as quality of governance, I find a positive and statistically significant relationship between the Bureaucratic Efficiency Index (the higher the Bureaucratic Efficiency Index the higher the quality of governance) and the ratio of the value added share of capital intensive goods to the value added share of labor intensive goods. The relationship remains positive and statistically significant even after controlling for the value of human capital, the value of the capital stock, primary school and secondary school enrolment, a measure of financial development, the number of employees, the average wage per employee, and whether a country is an oil producer. Predictions of our theoretical model plus our empirical analysis suggest that success in accumulating physical capital is not sufficient to achieve higher levels of productivity. Our model predictions suggest that differences in productivity and therefore output per worker across countries are driven primarily by differences in the quality of governance. A country’s long-run economic growth is determined primarily by the institutions and government policies that make up the economic environment.